The change in the yield structure elements of oilseed flax depending on hydrothermal conditions, the use of fertilizers, the seeding rates - Yu. V. Mamyrko; A. S. Bushnev (Зерновое хозяйство России, 2020)
The studies were conducted in the years of 2012–2017 in the zone of unstable moisture on leached blackearth (chernozem) in FSBSI FSC ARRIOC (Krasnodar). The object of research is the oilseed flax variety “ARRIOC 620”. In the variants of oilseed flax cultivation technology differing in the amount of fertilizer and the seeding rate, there were identified the biometric indicators and such yield structure elements as “plant height”, “length of a technical part of a stem”, “number of bolls per plant”, “number of plants”, “number of bolls”, “plant and seed weight per area unit”, “1000 seed weight”. There has been established that both fertilizers and seeding rate contributed to the variation of these indicators, which changed oilseed flax productivity. It has been found that productivity depends on moisture supply during the most important period of vegetation. In years with precipitation distribution characteristic for the arid zone of moistening (according to the STC), the productivity has been greatly affected by the moisture supply in May and June which corresponds to the growth stages “cotyledons – flowering”. In years with precipitation distribution characteristic for the humid and slightly arid zone of moistening (according to the STC), the productivity depended on the moisture supply in June, i. e. in the period “bud formation – flowering”.